Renal involvement as a unique manifestation of hemophagocytic syndrome - Roccatello, Dario; Sciascia, Savino; Barreca, Antonella; Naretto, Carla; Alpa, Mirella; Quattrocchio, Giacomo; Radin, Massimo; Fenoglio, Roberta (Frontiers in Medicine, 2022)
Renal-limited hemophagocytic syndrome (HPS) is a rare clinical setting characterized by abnormal activation of the immune system. Fever associated with pancytopenia, hepatosplenomegaly with liver dysfunction and hypofibrinogenemia are usually observed in HPS. From a histological level, the presence of nonmalignant macrophages infiltrating bone marrow and organs represent the hallmark of this condition. Nonmalignant macrophages are associate with phagocytosing activities involving other blood cells. While Primary HPS is usually associated with inherited dysregulation of the immune systems, secondary HPS usually occur in the context of infection or are linked to a neoplastic process. Clinical presentation varies and can potentially lead to life-threatening settings. While renal involvement has frequently been reported, however, detailed descriptions of the kidney manifestations of HPS are lacking. More critically, the diagnosis of HPS is rarely supported by renal biopsy specimens. We report four rare cases of biopsy-proven renal-limited HPS in patients presenting with acute kidney injury. The available evidence on this topic is critically discussed in light of the possible emergence of an autonomous entity characterized by an isolated kidney involvement without systemic manifestations.